International Research Network on Organizing by Projects (IRNOP) 2017 (UTS ePRESS, 2017)
Conference papers from the International Research Network on Organizing by Projects (IRNOP) conference, held at Boston University, USA on 11 to 14 June 2017. Host organization: Metropolitan College at Boston University, USA.